Harm reduction : a new direction for drug policies and programs - Erickson, Patricia G.; Riley, Diane M. (Diane Mary), 1953-; Cheung, Yuet-wah, 1952-; O'Hare, P. A. (Patrick Anthony), 1947-; International Conference on the Reduction of Drug-Related Harm 1994 : Toronto, Canada) (Toronto : University of Toronto Press, 1997)
This edited collection provides the latest in research and critical thinking on public health alternatives to conventional criminal approaches aimed at limiting the harms of both legal and illegal drugs for users and society.
Introduction: The Search for Harm Reduction -- 1. Case of the Two Dutch Drug-Policy Commissions: An Exercise in Harm Reduction, 1968-1976 / Peter D.A. Cohen -- 2. Legalization of Drugs: Responsible Action towards Health Promotion and Effective Harm Reduction Strategies / Line Beauchesne -- 3. Battle for a New Canadian Drug Law: A Legal Basis for Harm Reduction or a New Rhetoric for Prohibition? A Chronology / Benedikt Fischer -- 4. De-Medicalization of Methadone Maintenance / Marsha Rosenbaum -- 5. Readiness for Harm Reduction: Coming to Grips with the 'Temperance Mentality' / Bruce K. Alexander and Govert F. van de Wijngaart -- 6. Harm Reduction at the Supply Side of the Drug War: The Case of Bolivia / Fernando Garcia Arganaras -- 7. Harm Reduction, Human Rights, and the WHO Expert Committee on Drug Dependence / Robin Room -- 8. Harm Reduction, Doping, and the Clashing Values of Athletic Sports / Trudo Lemmens -- 9. Will Prisons Fail the AIDS Test? / Ralf Jurgens -- 10. Is Prenatal Drug Use Child Abuse?: Reporting Practices and Coerced Treatment in California / Amanda Noble -- 11. Towards a Harm Reduction Approach to Alcohol-Problem Prevention / Eric Single -- 12. Reducing Alcohol-Related Harm: A Balanced and Disaggregated Perspective / Martin Plant -- 13. Harm Reduction and Licensed Drinking Settings / Tim Stockwell -- 14. Reducing Alcohol-Related Harm in Communities: A Policy Paradigm / Claire Narbonne-Fortin, Rene Lauzon and Ronald R. Douglas -- 15. Harm Reduction and Alcohol Abuse: A Brief Intervention for College-Student Binge Drinking / G. Alan Marlatt and John S. Baer -- 16. Animal Self-Administration of Cocaine: Misinterpretation, Misrepresentation, and Invalid Extrapolation to Humans / John P. Morgan and Lynn Zimmer -- 17. Harm Reduction Interventions with Women Who Are Heavy Drinkers / Gerard J. Connors and Kimberly S. Walitzer -- 18. Two Steps Forward, One Step Back: Anti-User Bias in New York State's Approach to Needle Exchange / Rod Sorge and Ruth E. Harlow -- 19. Shopping, Baking, and Using: The Manufacture, Use, and Problems Associated with Heroin Made in the Home from Codeine-Based Pharmaceuticals / Julia Reynolds, Simon Lenton and Mike Charlton -- 20. 'Really Useful Knowledge': The Boundaries, Customs, and Folklore Governing Recreational Drug Use in a Sample of Young People / Laura Gamble and Michael George -- 21. Alcohol and Other Drug Use in the Punjabi Community in Peel, Ontario: Experiences in Ethnocultural Harm Reduction / Yuet W. Cheung, Timothy R. Weber and Purvi Biring -- 22. Female Drug Injectors and Parenting / Avril Taylor -- 23. Harm Reduction Model: An Alternative Approach to AIDS Outreach and Prevention for Street Youth in New York City / Michael C. Clatts, Edith Springer and W. Rees Davis -- 24. Working with Prostitutes: Reducing Risks, Developing Services / Sarah Crosby -- 25. Harm Reduction Approach to Treating Older Adults: The Clients Speak / Kathryn Graham, Pamela J. Brett and Jane Baron -- 26. Harm Reduction Efforts inside Canadian Prisons: The Example of Education / Andrea Riesch Toepell.
Online resource; title from PDF title page (EBSCO, viewed April 7, 2016).
"Collection of papers drawn from 7 international conferences on harm reduction."
"Selected, revised papers originally presented at the fifth International Conference on the Reduction of Drug Related Harm held in Toronto, Canada, 6-10 March 1994"--Introduction.
Includes bibliographical references.
JSTOR
Keywords: Drug abuse -- Prevention -- Congresses; Drug abuse -- Treatment -- Congresses; Drug abuse -- Government policy -- Congresses; Drug abuse -- Congresses; Social problems; Drug abuse -- Social aspects -- Congresses; Harm reduction -- Congresses; Drug abuse -- Prevention -- Congresses; Drug and Narcotic Control; Substance-Related Disorders -- rehabilitation; Legislation, Drug; Public Policy; Social Problems; Toxicomanie -- Congrès.; Toxicomanie -- Politique gouvernementale -- Congrès.; Toxicomanie -- Traitement -- Congrès.; Toxicomanie -- Prévention -- Congrès.; Toxicomanie -- Prévention -- Congrès.; Toxicomanie -- Traitement -- Congrès.; Toxicomanie -- Politique gouvernementale -- Congrès.; Toxicomanie -- Congrès.; Problèmes sociaux; Toxicomanie -- Aspect social -- Congrès.; Réduction des méfaits -- Congrès.; social issues; POLITICAL SCIENCE -- Public Policy -- Social Security; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; Harm reduction; Drug abuse -- Social aspects; Social problems; Drug abuse; Drug abuse -- Government policy; Drug abuse -- Prevention; Drug abuse -- Treatment; Conference papers and proceedings